Self-Esteem as a Mediator of Social Support and Health on Grandparents' Subjective Well-Being - Yupi, Emamiridya Erine; Lestari, Sri (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2025)
The elderly population in Indonesia and childcare are associated with subjective wellbeing (SWB) of grandparents. On the other hand, achieving SWB is important for living a mentally healthy life. Therefore, this research aimed to predict grandparents SWB through social support, physical health, and self-esteem. A quantitative correlational method was used with 350 respondents aged 45-75 years obtained by simple random sampling technique. Data collection used four instruments, including the SWB, social support, health status, and self-esteem scale, while data analysis was performed with path analysis. The results showed that social support, health, and self-esteem affected grandparents SWB directly and indirectly. The indirect path of self-esteem as a mediator contributed more than the direct path of social support and health status. The implication of this research is to improve grandparents SWB by strengthening intergenerational relationships as a form of providing meaningful social support. This offers opportunities for grandparents to contribute to the family and community, participate in various social activities, and easily access health facilities.